giải pt bằng cách đặt ẩn phụ: (x^2-2x+1)/(2x-3) = √(x+2)

Question

giải pt bằng cách đặt ẩn phụ: (x^2-2x+1)/(2x-3) = √(x+2)

in progress 0
Rylee 1 năm 2021-07-24T18:01:28+00:00 1 Answers 4 views 0

Answers ( )

    0
    2021-07-24T18:03:11+00:00

    Đáp án:

     

    Giải thích các bước giải:

    ĐKXĐ $: 2x – 3 \neq 0; x + 2 ≥ 0 ⇔ – 2 ≤ x < \dfrac{3}{2}; x >\dfrac{3}{2}$

    Đặt $y = \sqrt{x + 2} ≥ 0 ⇒ x = y² – 2 ⇒ 2x – 3 = 2y² – 7$

    $ PT ⇔ (x – 1)² = (2x – 3)\sqrt{x + 2}$

    $ ⇔ (y² – 3)² = (2y² – 7)y $

    $ ⇔ y^{4} – 6y² + 9 – (2y² – 7)y = 0$

    $ ⇔ 4y^{4} – 24y² + 36 – 4(2y² – 7)y = 0$

    $ ⇔ 4y^{4} – 28y² + 49 – 4(2y² – 7)y + 4y² = 13$

    $ ⇔ (2y² – 7)² – 4(2y² – 7)y + 4y² = 13$

    $ ⇔ (2y² – 2y – 7)² = 13$

    TH1 $: 2y² – 2y – 7 = \sqrt{13} ⇔ 2y² – 2y – 7 – \sqrt{13} = 0$

    $ ⇔ y = \dfrac{1}{2}(1 + \sqrt{15 + 2\sqrt{13}}) > 0$

    $ ⇔ x = y² – 2 = \dfrac{1}{2}(4 + \sqrt{13} + \sqrt{15 + 2\sqrt{13}})$

    TH2 $: 2y² – 2y – 7 = – \sqrt{13} ⇔ 2y² – 2y – 7 + \sqrt{13} = 0$

    $ ⇔ y = \dfrac{1}{2}(1 + \sqrt{15 – 2\sqrt{13}}) > 0$

    $ ⇔ x = y² – 2 = \dfrac{1}{2}(4 – \sqrt{13} + \sqrt{15 – 2\sqrt{13}})$

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )